Análise do Perfil do Vento em Condições Neutras no Centro de lançamento de Alcântara - Magnago, Roberto; Fisch, Gilberto; Fortes, Bianca; Oliveira, Paloma; Nogueira, Patrícia (Ciência e Natura, 2013)
In this study we present results of the logarithm of the wind profile, collected at the Centro de Lançamento de Alcântara (CLA) for five days in September 2008. The results show that the roughness length is of the order of 0.4 m and friction velocity is approximately 10% of the wind speed at 70 m. The wind profile obtained from an anemometric tower of 70 m with six levels of measurement fits well in logarithmic form.